Holistic Health in Children: Conceptualization, Assessment and Potential - Michaelson, Valerie (SpringerBriefs in Well-Being and Quality of Life Research,, 2018)
This book presents the results of the Canadian Holistic Health in Children project. Rooted in an ancient concept, this study addresses some novel thinking surrounding the assessment of health and its determinants in adolescent populations. Holism refers to the assessment of complex systems as composite wholes, instead of or in addition to their constituent parts. This idea is rarely applied to the study of health in children, and its application to adolescent populations represents a potentially important gap in knowledge. It fills this gap by conducting a series of analyses in a mixed methods paradigm. Quantitatively, it develops new measures and analytic strategies to be used in the assessment of health and its determinants in adolescents, and then applied these a series of national and cross-national studies. Qualitatively, it explores the origins and models of health inferred from existing theory as well as quantitative findings with groups of young people, and captures the richness of their stories in recurrent themes and metaphor. This book outlines the basic elements of theory that underlie holistic understandings of adolescent health, quantitative and qualitative findings, and then presents and interprets the results and translates them into a series of practical recommendations.